Correlation Analysis of Vestibular Symptoms and Migraine and Non-migraine Headaches: An Epidemiological Survey of 708 Female Nurses - Diao, Tongxiang; Zhu, Jinling; Yu, Lisheng; Ma, Xin (Frontiers in Neuroscience, 2022)
Objective: This study is oriented to study the correlation between different vestibular symptoms and migraine and non-migraine headaches. Methods: A questionnaire containing factors related to vestibular symptoms and migraine was designed to survey nurses in a tertiary hospital. Then, all study subjects were divided into three groups: no headache, migraine, and non-migraine headache, and the general physical condition and incidence of different vestibular symptoms were compared among the three groups. Results: Of all the 708 subjects, 233 had headaches. The incidence of migraine was 13.3%. There were 235 cases had vestibular symptoms Dizziness and vertigo are independent factors related to headaches, especially migraine. The risk of migraine and other types of headaches in the vertigo group is 2.808 and 2.526 times of those without vertigo, and in the dizziness group is 8.248 and 5.732 times of those without dizziness. Conclusions: Different vestibular symptoms were all related to migraine. And different vestibular symptoms and non-migraine headaches also showed a clear correlation.